2017
DOI: 10.1116/1.4979047
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the density, optical polarizabilities, and crystallinity of TiO2 thin films deposited via atomic layer deposition from 38 to 150 °C using the titanium tetrachloride-water reaction

Abstract: Refractive index, density, and optical polarizabilities as a function of atomic layer deposition (ALD) growth temperature for titanium dioxide (TiO2) thin films are reported for the first time between 38 and 150 °C using the titanium tetrachloride-water reaction. Consistent with prior reports, Raman spectroscopy and x-ray diffraction indicate that the films are amorphous below 150 °C and form the crystalline anatase phase at deposition temperatures at or above 150 °C. Despite this change in atomic structure, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…It is reported that the density of TiO 2 films generally increases with the refractive index [ 43 ]. The films annealed at 550–750 °C have the highest refractive index, which is similar to those of high-quality PEALD TiO 2 films with a corresponding film density of 3.8 g/cm 3 [ 43 ]. In comparison, the sol-gel spin-coated TiO 2 films have refractive indices typically under 2.2 [ 44 , 45 ], corresponding to a density of 2.95 g/cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the density of TiO 2 films generally increases with the refractive index [ 43 ]. The films annealed at 550–750 °C have the highest refractive index, which is similar to those of high-quality PEALD TiO 2 films with a corresponding film density of 3.8 g/cm 3 [ 43 ]. In comparison, the sol-gel spin-coated TiO 2 films have refractive indices typically under 2.2 [ 44 , 45 ], corresponding to a density of 2.95 g/cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the crystallization temperature matches the temperature at which the refractive index of the thin films starts to rise. However, amorphous films present a lower refractive index than their crystalline counterparts [ 25 , 26 , 27 , 30 ] and are therefore less sought for application as photonic crystal-based reflectors, but they are interesting for applications such as antibacterial films or oxygen sensors [ 56 ]. Moreover, the compositions with less than 14% of alumina, including the pure titania one, could be attractive for photocatalysis applications, as the anatase phase often exhibits higher photocatalytic activity than the rutile phase [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the latter one is of interest for optical applications since titania features a relatively high refractive index, often higher than 2.3 at 632.8 nm. The exact refractive index value is known to vary depending on the deposition temperature and the ALD precursor used to grow the film [ 25 , 26 , 27 , 28 ]. Moreover, it also depends on the crystalline phase, as well as the overall film density [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These thicknesses are based upon spectroscopic ellipsometry measurements made on silicon monitor wafers included in the ALD reactor with the nanopaper and the cumulative ALD literature that has shown these processes to have self-limited growth rates of $0.11 nm per cycle (TMA-H 2 O) and 0.6 nm per cycle (TiCl 4 -H 2 O). 26 Furthermore, both Al and Ti characteristic X-rays were undetectable with EDX spectroscopy, indicating that these coatings are well below the detection limit of this analysis technique ($0.01 wt%).…”
Section: Basic Structural and Chemical Characterization Of Untreated mentioning
confidence: 92%